Profiling of the micro-RNA landscape in human vascular smooth muscle cells and exosomes during replicative senescence - Nguyen, Duong Ngoc Diem (2021)
Vascular aging is highly associated with cardiovascular morbidity and mortality and vascular smooth muscle cell (VSMC) senescence is one of its key contributors. During senescence, VSMCs intracellular regulations as well as intercellular communication are altered. However, intracellular and intercellular signaling in senescent VSMCs are not fully explored. Micro-RNAs (miRNAs) cellular posttranscriptional regulators as well as potential intercellular messengers and understanding miRNA intracellular and intercellular regulation via the exosomal axis during VSMC senescence may elucidate the molecular mechanistic link between vascular aging and early adverse vascular remodeling. This study aimed to identify dysregulated miRNA expression within senescent VSMCs as well as senescent VSMC-derived exosomes. Healthy and senescent human VSMCs (hVSMCs) were cultured in vitro and exosomes secreted by these cells were isolated via ultracentrifugation. Subsequently, cellular and exosomal miRNAs were isolated and used for library preparation of whole-genome small RNA next-generation sequencing (NGS). Post-sequencing and differential expression analyses compared the miRNA profiles between healthy and senescent hVSMCs as well as their derived exosomes. Thereafter, NGS data were validated using real-time polymerase chain reaction (qPCR). Additionally, target prediction, gene ontology and pathway enrichment analyses were performed. In senescent hVSMCs, eight significant differentially expressed mature miRNAs were identified (n= 4, q <0.05). Bioinformatic analyses showed correlation between upregulated miRNAs, hsa-miR-664a-3p, hsa-miR-664a-5p, hsa-miR-664b-3p and hsa-miR-4485-3p, with altered cellular metabolism and transport, with changes in ATP binding and reduced stress response. Meanwhile, downregulated miRNAs, hsa-miR-155-5p and hsa-miR-20a-5p might associate with cell cycle arrest at G1/S phase, reduced stress response and increased levels of oxidative stress. On the other hand, three significant differentially expressed miRNAs were found in senescent hVSMC-derived exosomes. Data suggested that the upregulated exosomal miRNA hsa-miR-7704 might involve in intercellular communication via the exosomal signaling axis. Concurrently, downregulation of exosomal miRNAs hsa-miR-155-5p and hsa-miR-146b-5p promoted cell cycle arrest and evaded from immune clearance. Interestingly, there was a consistent observation of hsa-miR-155-5p downregulation in both senescent hVSMCs and their secreted exosomes. Further analyses with the other dysregulated miRs suggested hsa-miR-155-5p involvement in the Smad/TGF-beta and PI3K/Akt/mTOR signaling pathways. Differentially expressed intracellular and exosomal miRNAs might be involved in the regulation of cell survival in senescent hVSMCs via the TGF-beta signaling pathway. Finally, changes in miRNA signaling in senescent hVSMCs reflected association with vascular aging and therefore might pose as a potential link between early vascular aging and cardiovascular diseases.